Hospitality and tourism industry in international business - Shapoval, V. S.; Pererva, P. G. (My University, 2023)
Studies show that the problem of quality control is quite acute in the provision of services. First of all, this is a problem of self-control of the work of service personnel, provided that each employee knows how to ensure adequate quality assurance.
Індустрія гостинності та туризму міжнародному бізнесі
Keywords: business; international activity; tourism; hospitality; enterprises